Peranan Dinas Sosial Menyalurkan Bantuan Pangan Non Tunai (Bpnt) (Penelitian Pada Dinas Sosial Kabupaten Deli Serdang) - Anwar, Aslihal; Muda, Indra; Batubara, Beby Masitho (Jurnal Ilmiah Administrasi Publik dan Pemerintahan (JIAPP), 2024)
Non-cash Food Assistance (BPNT) is food assistance distributed non-cash to Beneficiary Families every month in the amount of Rp. 110,000 / KPM. The problem in this research is how the role of social services in distributing BPNT and what is damaged in distributing BPNT. To obtain data in this study using qualitative descriptive methods, observation, and documentation. This study involved 6 information, namely 1 key informant, 1 main informant and 4 additional informants. Based on the research results, the Social Service has a role in distributing BPNT, starting from coordinating planning, carrying out data validation and updating, providing companions. socialization has been carried out, but local officials are still not effective in determining the participants of the socialization. Planning, Monitoring and evaluation, Procurement of complaints. Coaching, and reporting on implementation. The fleas in distributing BPNT are: not on target, not entering the Integrated Database (BDT), data not found, incomplete population administration, late arrival of assistance. Based on the results of the study, it can be ignored that the Social Service has a role in distributing BPNT, starting from planning coordination, updating data, providing companions, socialization, planning, evaluation, complaint procurement, reporting. As it progressed, assistance came from the Deli District Social Service in distributing BPNT, among others: Not on target, not entering BDT, data not found, incomplete population administration and delayed assistance.